Rozwijanie umiejętności językowych i komunikacyjnych dziecka. Wybrane aspekty - Redakcja (Wydawnictwo Naukowe UAM, 2017)
The monograph comprises eighteen interdisciplinary texts with a significant cognitive and reflective value. Their authors have taken up the topic of linguistic complexity and communicative problems associated with childhood, provoking the reader to engage in a multi-faceted discourse. Linguistic and communicative competence, both with respect to the mother tongue and a foreign language (or foreign languages) opens us to the world: it expands the boundaries of our cognition, as it involves not only the acquisition of purely linguistic, but also psychological, social and cultural knowledge. Consequently, the level of linguistic and communicative proficiency implies the child’s rapid growth of intelligence and knowledge, and improves their self-esteem and sense of competence and selfefficacy. Successful linguistic and communicative competence impinges on the child’s advantageous position at preschool and in the school classroom, influences the child’s level of satisfaction with new interpersonal relations, determines school performance and contributes to future career success. The development of these skills requires stimulation and reinforcement of children’s motivation to learn their mother tongue and foreign languages based on the influences of the family environment and educational (preschool and school) settings. Therefore, it cannot be stressed enough how important it is to provide children with proper conditions for acquiring experiences in this scope, enabling them to discover strategies for learning (a) language(s) and feel satisfaction with their activity and its results, lying at the base of broadly understood language pedagogy. The topics are addressed in this publication, and explored in succession within four thematic sections including 1) Foundations of the child’s linguistic and communicative development, 2) The child’s linguistic activities in selected contexts, 3) Properties of language and factors determining the child’s linguistic and communicative competence, 4) Development of the child’s linguistic and communicative skills in a foreign language.

Monografia zawiera osiemnaście interdyscyplinarnych tekstów o znaczącym walorze poznawczym i refleksyjnym, w których autorzy podejmują kwestię złożoności językowej i komunikacyjnej problematyki okresu dzieciństwa, prowokując czytelnika do wieloaspektowego dyskursu. Sprawność językowa i komunikacyjna zarówno w zakresie języka rodzimego, jak i języka obcego (czy języków obcych) otwiera nas na świat – rozszerza granice naszego poznania łącząc się nie tylko ze zdobywaniem wiedzy czysto lingwistycznej, ale również psychologicznej, socjologicznej i kulturowej. Dlatego poziom umiejętności językowych i komunikacyjnych implikuje u dziecka szybki wzrost inteligencji i wiedzy, zapewnia mu poczucie własnej wartości i poczucie kompetencji oraz skuteczności w działaniu. Sukcesy w zakresie sprawności językowej i komunikacyjnej decydują o korzystnej pozycji dziecka w przedszkolu i klasie szkolnej, warunkują poziom jego satysfakcji z nawiązywanych relacji interpersonalnych, jak również decydują o osiągnięciach szkolnych i sprzyjają uzyskiwaniu sukcesów zawodowych w przyszłości. Rozwój wspomnianych umiejętności wymaga stymulacji, kształtowania motywacji dzieci do uczenia się języka ojczystego, a także języków obcych w oparciu o oddziaływania środowiska rodzinnego, jak i środowisk edukacyjnych (przedszkola i szkoły). Nie do przecenienia jest zatem zapewnianie dzieciom odpowiednich warunków do zdobywania doświadczeń w tym zakresie, umożliwiających odkrywanie strategii uczenia się języka (języków), a także odczuwanie satysfakcji z własnej działalności i jej wyników, leżących u podstaw szeroko rozumianej pedagogiki językowej. Kwestie te podejmuje niniejsza publikacja, ukazująca je kolejno w czterech obszarach tematycznych, jakimi są: 1) Podstawy rozwoju językowego i komunikacyjnego dziecka, 2) Czynności językowe dziecka w wybranych kontekstach, 3) Właściwości języka i uwarunkowania kompetencji językowych oraz komunikacyjnych dziecka, 4) Rozwijanie umiejętności językowych i komunikacyjnych dziecka w obszarze języka obcego.
The development of the child’s linguistic and communicative skills. Selected aspects
Keywords: kompetencje językowe; kompetencje komunikacyjne; sprawności językowe; język i mowa; twórczy wymiar aktywności językowej dzieci